PELAKSANAAN TUGAS DAN FUNGSI PEMERINTAH DALAM USAHA KESEJAHTERAAN SOSIAL ANAK - Budi Astuti (Jurnal Hukum, 2019)
The research objective was to determine the process of social welfare services carried out by the Woro Wiloso Salatiga Social Rehabilitation Center in realizing children's social welfare, and to find out the efforts taken by the Woro Wiloso Social Rehabilitation Center in overcoming obstacles in social services This research methodology uses the approach of juridical sociology with descriptive of research type. The method of collecting data uses observation and interview. The method of analyze data uses qualitative description. The writer applied the theory of good governance and public service to observe whether or not the undertaking of social service in the social service office â€œWoro Wilosoâ€ Salatiga has fulfilled the aspect andÂ  function ofÂ  good governance and public service as the efforts in improving the children welfare to reach the success of the development of social welfare in Central Java.